Head of the chair of general surgery, medical school dean, vice chancellor, rector of the Imperial University of Moscow Arkady A. Alfonsky and his role in improving the teaching of clinical disciplines and the development of the medical faculty - V. K. Gostishchev; М. А. Evseev (Сеченовский вестник, 2013)
This article provides information about the role of Arkady A. Alfonsky — head of the chair of general surgery, medical school dean, vice chancellor, rector of the Imperial University of Moscow — in the development and improvement of medical education in Russia.